Experimental design : from user studies to psychophysics - Cunningham, Douglas W. [ (Douglas William)]; Wallraven, Christian (An A K Peters book, 2012)
This book explains the basic terminology used to discuss experiments and takes a brief look at the more than 150 year history has in psychology. It covers how to generalize from a few people to the whole population. The largest part of the book is dedicated to the most flexible, and arguably the most central, aspect of an experiment: what do the participants do? Each chapter follows the same structure and includes two examples, one from traditional psychophysics and on using computer animated facial expressions as stimuli